DISTRIBUTION AND HABITAT OF CARABUS HUNGARICUS (COLEOPTERA: CARABIDAE) IN SERBIA AND RECOMMENDATION FOR MONITORING (Acta Entomologica Serbica, 2023)
The distribution of Carabus hungaricus in Serbia has not been summarized so far. There are only a few published records of this beetle in Serbia. Due to new findings, it was necessary to update the distribution of this species in Serbia. Recent field research revealed that the largest suitable habitat is the Deliblato Sands in the South Banat District, where this species is common. Other important areas are located near the Romanian border in the vicinity of the city of Vršac and near Mužlja (in the neighborhood of the city of Zrenjanin, Central Banat District), where the northernmost population in Serbia is located. In addition to this overview of distribution, we propose monitoring methodology for C. hungaricus. We believe that regular monitoring can bring the necessary attention to the disappearing steppe habitats and that the results can help to manage them appropriately in the future.